The Scholarship of Critique and Power - Martin-Thomsen, Tiona Camille; Scagnetti , Gaia; McPhee, Siobhan R.; Akenson, Ashley B.; Hagerman, Dana (Teaching and Learning Inquiry, 2021)
Critique can be defined as disciplinary feedback, analysis, or assessment provided to an individual or within a group, be it a classroom or a team. At a fundamental level, it is an exchange of ideas, impressions, evaluations, opinions, reflections, judgments, speculations, or suggestions to oneself or between two or more participants in a defined context. Scholars describe critique as a signature pedagogy in many disciplines, a cornerstone of the educational experience. There has been scant critical analysis of how critique also represents a performance of power with roots in positions of authority, expertise, or assigned roles. Such power dynamics have been explored in some areas within SoTL, for example in scholarship on assessment, epistemic disobedience, social justice, feminist pedagogies, and critical race theory. However, this has generally not been the case within the scholarship on critique. To better understand the dimensions of power in the context of critique we developed a conceptual framework that can be applied at the individual level (teacher to student, student to student) as well as the systemic level (critique as a construct of cultural hegemony in a specific episteme). Drawing from theoretical and pedagogical literature in areas such as cultural studies, whiteness studies, design education, and assessment, the conceptual framework defines power in three main expressions: power as inequity, power as authority, and power as cultural hegemony. The framework can be used to identify and define power within the critique context and to also inform reflection and shift perspectives at various academic levels.